2010
DOI: 10.1111/j.1471-4159.2010.06588.x
|View full text |Cite
|
Sign up to set email alerts
|

Both synthesis and reuptake are critical for replenishing the releasable serotonin pool in Drosophila

Abstract: Synthesis and reuptake regulate 5-HT release | 189 25-30 min prior to the initiation of experiments, a time that is sufficient for drugs to diffuse into the nerve cord (Borue et al. 2009). An electrode was implanted in the neuropil using a micromanipulator and allowed to equilibrate for 5 min before data were collected. After the collection of at least 30 s of baseline data, VNCs were exposed to 10 s of intense blue light to stimulate release. This stimulation length produces close to maximal serotonin release… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 51 publications
1
62
0
Order By: Relevance
“…31,48 Increased synthesis could contribute to an increase in the readily releasable pool of serotonin; this pool is known to be sensitive to changes in uptake and synthesis. 49 Although the current study does not provide direct evidence for differences in serotonin release per se, we hypothesize that presynaptic serotonin 1A autoreceptor desensitization/downregulation, 47,50 in conjunction with increased synthesis, 48 Mice genetically lacking SERT were previously discovered to show a loss of frequency-dependent serotonin release when brain slices containing the substantia nigra were investigated by FSCV. 51 The authors concluded that abolishing SERT leads to a large summation of extracellular serotonin regardless of stimulus strength.…”
Section: Resultsmentioning
confidence: 92%
“…31,48 Increased synthesis could contribute to an increase in the readily releasable pool of serotonin; this pool is known to be sensitive to changes in uptake and synthesis. 49 Although the current study does not provide direct evidence for differences in serotonin release per se, we hypothesize that presynaptic serotonin 1A autoreceptor desensitization/downregulation, 47,50 in conjunction with increased synthesis, 48 Mice genetically lacking SERT were previously discovered to show a loss of frequency-dependent serotonin release when brain slices containing the substantia nigra were investigated by FSCV. 51 The authors concluded that abolishing SERT leads to a large summation of extracellular serotonin regardless of stimulus strength.…”
Section: Resultsmentioning
confidence: 92%
“…Homozygous 3-day-old larvae expressing a Tph-GAL4;UAS-ChR2 genotype were fed all-trans retinal for two days 25,26 . The central nervous system (CNS) of a wandering, 3 rd instar (5-day-old) larvae was dissected and incubated as described previously 27 .…”
Section: Methodsmentioning
confidence: 99%
“…The fruit fly also offers considerable advantages, as locomotor circuits of the larva are well studied [90, 91] and genetic amenability not only provides access to specific gene function but also allows cell-labeling techniques crucial for circuit observation. Electrochemical techniques such as fast scan cyclic voltammetry have been modified to measurereal-time serotonin release in Drosophila larval CNS [92,93], meaning that serotonergic input and locomotor output [90] could be quantified simultaneously in addition to monitoring morphology of the serotonergic neurons and the locomotor circuit.…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%